A Composite Histopathologic Invasion Score Predicts Lymph Node Metastasis in Gastric Cancer - Ebru Karcı; Mahya Ahmadpour Youshanlui; Ferhat Ozden; Ozgur Acikgoz; Ömer Fatih Ölmez; Ozcan Yildiz; Hafize Uzun; Ahmet Bilici (Journal of Clinical Medicine, 2026)
Background: Lymph node metastasis (LNM) is a major determinant of prognosis in gastric adenocarcinoma. Although lymphovascular invasion (LVI) and perineural invasion (PNI) are established markers of aggressive tumor behavior, their combined association with nodal dissemination has not been systematically evaluated. This study investigated the relationship between invasive histopathologic features and LNM and developed a composite invasion score. Methods: This retrospective study included 395 patients with gastric adenocarcinoma. Clinicopathological analyses involving LNM were performed in the surgical resection cohort. A composite invasion score (0–2) was generated based on the presence of LVI and PNI. Associations with LNM, metastatic lymph node burden, and lymph node ratio (LNR) were evaluated using non-parametric tests and multivariable logistic regression. Predictive performance was assessed using receiver operating characteristic (ROC) analysis. An exploratory external transcriptomic analysis was performed using the GSE15459 dataset. Results: Both LVI and PNI were significantly associated with LNM (both p < 0.001). The composite invasion score showed a stepwise association with nodal dissemination, with median metastatic lymph node counts increasing from 0 in score-0 tumors to 3.5 in score-1 and 9 in score-2 tumors (p < 0.001). After adjustment for pathological T stage, histological grade, Lauren classification, age, and tumor location, the composite invasion score remained an independent predictor of LNM (OR = 4.53, 95% CI: 1.81–13.00, p = 0.002). LNR also increased significantly across score categories (p < 0.001). The composite invasion score demonstrated good discriminatory performance for LNM (AUC = 0.848, 95% CI: 0.773–0.923). The exploratory transcriptomic analysis demonstrated significant upregulation of MMP11, MMP14, and FAP in advanced-stage tumors, consistent with increased extracellular matrix remodeling and stromal activation. Conclusions: A simple composite invasion score integrating LVI and PNI is independently associated with lymph node metastasis and metastatic burden in gastric adenocarcinoma. The accompanying exploratory transcriptomic analysis provides biological context for these clinicopathological findings by demonstrating stage-associated extracellular matrix remodeling rather than direct molecular validation of the proposed score. These findings support the potential utility of the composite invasion score as a postoperative pathology-derived risk stratification tool.